Assessing the impact of understory vegetation cut on soil epigeic macrofauna from a cork-oak Montado in South Portugal - Mendes, Sara Margarida; Santos, Joaquim; Freitas, Helena; Sousa, José Paulo (Agroforestry Systems, 2011)
Cork oak ‘‘Montados’’ are a particular Mediterranean ecosystem, which can be found in Southern Portugal. Portuguese ‘‘Montados’’ are manmade ecosystems, mainly used for cork production and cattle farming, that support a high biological diversity. Current sustainable management techniques imply a shrub clearing with heavy machinery, which can be highly disruptive for soil biota. In order to evaluate the effects of understory vegetation management on soil epigeic macrofauna, ﬁve zones were deﬁned along a chronosequence of shrub clearing: a non-disturbed zone (zone 5) and zones where understory vegetation was cut at 4–5 years (zone 4), at 3–4 years (zone 3), at 2 years (zone 2) and at 1 year (zone 1). A sixth zone (zone 6) was selected in a pasture, where cattle are occasionally present. Soil fauna was sampled using ‘‘pitfall’’ traps and sampling took place in autumn 2003. A total of 2,677 individuals, separated into 152 species and morphospecies, were caught in the traps. With the exception of zone 6, that presented a lower number of species, all the other zones from the chronosequence presented, in most cases, a similar number of taxa, species diversity (Shannon) and species richness (Margalef). Multivariate analysis separated recently disturbed zones (plus zone 6) from those intervened at longer time; groups like Formicidae, Scydmaenidae, most families from Araneae and insect larvae appeared closely associated to zones 3–5 (with a higher shrub cover and thick litter layers), whereas, other Hymenoptera, Gastropda and most Coleoptera families, appeared associated to recently disturbed zones (zones 1 and 2) and to zone 6, characterized by a lower shrub cover and a lower accumulation of litter. This separation indicates that effects of the intervention can endure for 2 or 3 years. After that time, the normal natural regeneration of the understory vegetation seems to support the restoration of the macrofauna community, thus indicating that the sustainable management strategy adopted, i.e., making a shrub cut every 5–6 years, seems not induce a signiﬁcant effect on local species richness of soil epigeic macrofauna.
Keywords: Biodiversity; cork-oak forests; soil macrofauna; sustainable management; understory management